Davis, ou le bonheur d'être fou comédie-vaudeville en deux actes - Fournier, Narcisse 1803-1880 (Marchant, 1842)
Item no. 928 in Two centuries of French drama, 1760-1960, a collection of 2,014 French dramas housed in the Department of Special Collections, University of Florida Libraries.